The Biocompatibility of Degradable Magnesium Interference Screws: An Experimental Study with Sheep. (31st January 2015) - Thormann, Ulrich; Alt, Volker; Heimann, Lydia; Gasquere, Cyrille; Heiss, Christian; Szalay, Gabor; Franke, Jörg; Schnettler, Reinhard; Lips, Katrin Susanne
Abstract : Screws for ligament reconstruction are nowadays mostly made of poly-L-lactide (PLLA). However, magnesium-based biomaterials are gathering increased interest in this research field because of their good mechanical property and osteoanabolic influence on bone metabolism. The aim of this pilot study was to evaluate the biocompatibility of an interference screw for ligament reconstruction made of magnesium alloy W4 by diecasting and milling and using different PEO-coatings with calcium phosphates. PLLA and titanium screws were used as control samples. The screws were implanted in the femur condyle of the hind leg of a merino sheep. The observation period was six and twelve weeks and one year. Histomorphometric, immunohistochemical, immunofluorescence, and molecular biological evaluation were conducted. Further TEM analysis was done. In all magnesium screws a clinically relevant gas formation in the vicinity of the biomaterial was observed. Except for the PLLA and titanium control samples, no screw was fully integrated in the surrounding bone tissue. Regarding the fabrication process, milling seems to produce less gas liberation and has a better influence on bone metabolism than diecasting. Coating by PEO with calcium phosphates could not reduce the initial gas liberation but rather reduced the bone metabolism in the vicinity of the biomaterial.